PENGARUH SISTEM INFORMASI AKUNTANSI DAN SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN (SURVEY PT. SRIWIJAYA CONTAINER) - Dela Rizky Amalia; Harsi Romli; Mutiara Kemala Ratu (Universitas Dian Nuswantoro, 2023)
This thesis aims to determine the Effect of Accounting Information Systems and Human Resources on the Quality of Financial Reports at PT. Sriwijaya Container. The problem that occurs is that the educational background of employees is still not in accordance with the task section and the accounting information system used cannot be accessed by the general public. In this study, the research method used was a quantitative method, namely the method of collecting data in the form of numbers and the analysis used was multiple regression using SPSS 26. Based on the results of this study indicate that simultaneously (Test F) accounting information system variables and the quality of human resources affect the quality of financial reports. Partially (T test) the accounting information system variable has no effect on the quality of financial reports, while the human resources variable has an effect on the quality of financial reports.